Posttraumatic stress disorder and its cross-generational familial relationship with drug use disorder and alcohol use disorder: an extended Swedish adoption study - Ananda B. Amstadter; Linda Abrahamsson; Shannon Cusack; Jan Sundquist; Kenneth S. Kendler; Kristina Sundquist (European Journal of Psychotraumatology)
Objective: Information on how parental risk for posttraumatic stress disorder (PTSD) relates to their children’s risk for drug use disorder (DUD) and alcohol use disorder (AUD) is limited. This study is the first to utilize an extended adoption design which can address questions about the degree of, and sources of, cross-generational and cross-disorder transmission of PTSD and substance use disorders.Method: We examined diagnoses using Swedish National registries for parents and their adult offspring (n = 2,194,171, born 1960–1992) from six types of families (intact (1), not lived with biological father (2) or mother (3), step father (4), step mother (5), and adoptive (6)). Parent–child resemblance was assessed by tetrachoric correlation.Results: PTSD and DUD showed an approximately symmetrical cross-generational cross-disorder relationship. Conversely, AUD in parents was more related to the risk for PTSD in offspring compared to the reverse direction. The cross-disorder cross-generation transmission correlations for PTSD to DUD were higher than those for PTSD to AUD. Genetic and rearing correlations for PTSD-DUD were estimated at + .79 (CI: .66, .91) and + .49 (CI: .33, .65), significantly higher than those for PTSD-AUD + .59 (CI: .48, .71) and + .28 (CI: .12, .44).Conclusions: PTSD and the substance use disorders demonstrated cross-transmission, but more so for DUD. PTSD and DUD demonstrated highly correlated genetic effects, and moderately correlated rearing effects. Correlations of genetic and rearing effects between PTSD and AUD were lower than those for PTSD and DUD.